PENGGUNAAN MEDIA PEMBELAJARAN INFOGFRAFIS UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI SISWA PADA MATERI KEUNIKAN KEBIASAAN MASYARAKAT DI SEKITARKU SISWA KELAS IV SDN CILAKU KOTA SERANG - Selly Melianda; Beni Junedi; Ratna Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted based on the problem of low communication skills among fourth-grade students at SDN Cilaku Kota Serang in the social studies subject "Unique Customs of the Community Around Me." This low skill level is thought to be influenced by the lack of use of interesting visual learning media in the learning process. The purpose of this study was to determine the effect of using infographics on improving students' communication skills. This study employed a quantitative approach with a pre-experimental design of the one- group pretest-posttest type. The research subjects consisted of 15 students selected through purposive sampling. The research instruments consisted of an essay test to measure students' communication skills and a questionnaire to collect their responses to the media used. The analysis results showed an improvement in communication skills after the use of infographic media, as indicated by the difference in pretest and posttest scores and moderate N-Gain scores. Additionally, student responses indicated that infographics facilitated understanding of the material and made learning more interesting. It can be concluded that infographic learning media proved to be effective in improving students' communication skills in the material on the uniqueness of the customs of the community around me, and the student response questionnaire met good criteria.